2016
DOI: 10.1021/acs.inorgchem.6b00244
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Trends in Lanthanide Compounds through the Eyes of Multireference ab Initio Theory

Abstract: Regularities among electronic configurations for common oxidation states in lanthanide complexes and the low involvement of f orbitals in bonding result in the appearance of several periodic trends along the lanthanide series. These trends can be observed on relatively different properties, such as bonding distances or ionization potentials. Well-known concepts like the lanthanide contraction, the double-double (tetrad) effect, and the similar chemistry along the lanthanide series stem from these regularities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 65 publications
11
108
0
Order By: Relevance
“…In this way, experimentally derived parameters as zero-field splitting D and E, effective g-factors, and Racah and ligand field parameters can be directly compared with their calculated counterparts. In many cases, data from magnetic measurements is not enough to fit a consistent parameter set in a univocal way, which can be estimated by electronic structure methods [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, experimentally derived parameters as zero-field splitting D and E, effective g-factors, and Racah and ligand field parameters can be directly compared with their calculated counterparts. In many cases, data from magnetic measurements is not enough to fit a consistent parameter set in a univocal way, which can be estimated by electronic structure methods [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The one-electron character of crystal field theory is discussed and shown to be valuable, although it is not completely quantitative. [20,21] The first-principles methodS O-CASSCF( complete active space self-consistentf ield theory with at reatment of the spinorbit (SO) coupling by state interaction) has shown its capability,i nm any cases, to reproduce the magnetic data of the complexes, and give further physical insights, especially regarding the nature of the ground and excited states, into the direction of the magnetic moment and the energetic spectrum and chemicalb onding. In the case of aromaticl igands, it is necessary to add more parameters (a displacementp arameter) to mimict he covalency.…”
mentioning
confidence: 99%
“…[14] First-principles calculations are regularly used to quantify the degree of covalencyi nm etal-ligand bonding. [20,21] The first-principles methodS O-CASSCF( complete active space self-consistentf ield theory with at reatment of the spinorbit (SO) coupling by state interaction) has shown its capability,i nm any cases, to reproduce the magnetic data of the complexes, and give further physical insights, especially regarding the nature of the ground and excited states, into the direction of the magnetic moment and the energetic spectrum and chemicalb onding. [20,21] The first-principles methodS O-CASSCF( complete active space self-consistentf ield theory with at reatment of the spinorbit (SO) coupling by state interaction) has shown its capability,i nm any cases, to reproduce the magnetic data of the complexes, and give further physical insights, especially regarding the nature of the ground and excited states, into the direction of the magnetic moment and the energetic spectrum and chemicalb onding.…”
mentioning
confidence: 99%
“…Due to the rapid development of theoretical chemical technologies and computation ability, more and more theoretical studies of Ln complexes have been reported in the past 30 years. Combined with the effective core potential, Density Functional Theory has been proved to be a powerful tool for determining different Ln‐complexes’ structures, bonding nature, stability and other properties . Using DFT, Wipff and co‐workers systematically studied the structures, Ln−L interaction, and energy features of Ln complexes formed with phosphoryl ligands .…”
Section: Introductionmentioning
confidence: 99%